Effects of in-season enhanced negative work-based vs traditional weight training on change of direction and hamstrings-to-quadriceps ratio in soccer players - Coratella, G.; Beato, M.; Cè, E.; Scurati, R.; Milanese, C.; Schena, F.; Esposito, F. (Biology of Sport, 2019)
The present study investigated the effects of in-season enhanced negative work-based training (ENT) vs weight training in the change of direction (COD), sprinting and jumping ability, muscle mass and strength in semi-professional soccer players. Forty male soccer players participated in the eight-week, 1 d/w intervention consisting of 48 squat repetitions for ENT using a flywheel device (inertia=0.11 kg·m-2) or weight training (80%1 RM) as a control group (CON). Agility T-test, 20+20 m shuttle, 10 m and 30 m sprint, squat jump (SJ) and countermovement jump (CMJ), lean mass, quadriceps and hamstrings strength and the hamstrings-to-quadriceps ratio were measured. Time on agility T-test and 20+20 m shuttle decreased in ENT (effect-size =-1.44, 95% CI -2.24/-0.68 and -0.75, -1.09/-0.42 respectively) but not in CON (-0.33, -0.87/0.19 and -0.13, -0.58/0.32). SJ and CMJ height increased in both ENT (0.71, 0.45/0.97 and 0.65, 0.38/0.93) and CON (0.41, 0.23/0.60 and 0.36, 0.12/0.70). Overall, quadriceps and hamstrings strength increased in both ENT and CON (0.38/0.79), but the hamstrings-to-quadriceps ratio increased in ENT (0.31, 0.22/0.40) but not in CON (0.03, -0.18/0.24). Lean mass increased in both ENT (0.41, 0.26/0.57) and CON (0.29, 0.14/0.44). The repeated negative actions performed in ENT may have led to improvements in braking ability, a key point in COD performance. Semiprofessional soccer players may benefit from in-season ENT to enhance COD and the negative-specific adaptations in muscle strength and hamstrings-to-quadriceps ratio.